2019
DOI: 10.20960/nh.02791
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity attitudes, food symptomatology and meanings associated with obesity in students linked to the health area

Abstract: Abilés Osinaga J. 25-hydroxy vitamin D and syndrome metabolic components in candidates to bariatric surgery. Nutr Hosp 2016;33:43-46 Palabras clave: Vitamina D. Cirugía bariátrica. Obesidad mórbida. Síndrome metabólico. ResumenObjetivo: el objetivo de este estudio fue evaluar la prevalencia de hipovitaminosis D en los candidatos a cirugía bariátrica (CB) y su relación con factores de riesgo y los componentes del síndrome metabólico. Material y métodos: los parámetros clínicos, antropométricos y bioquímicos se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Among others, drivers of weight stigma manifestations that were investigated included factors such as socioeconomic status, participants’ BMI, participants’ feelings about their own weight, exposure to people with obesity (such as having someone with obesity in the family), participants’ attitudes toward obesity itself, and attitudes of participants’ family members toward people with obesity. For example, a study [ 16 ] with healthcare students in Chile found that having a desire for thinness predicted antiobesity attitudes.…”
Section: Resultsmentioning
confidence: 99%
“…Among others, drivers of weight stigma manifestations that were investigated included factors such as socioeconomic status, participants’ BMI, participants’ feelings about their own weight, exposure to people with obesity (such as having someone with obesity in the family), participants’ attitudes toward obesity itself, and attitudes of participants’ family members toward people with obesity. For example, a study [ 16 ] with healthcare students in Chile found that having a desire for thinness predicted antiobesity attitudes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, one possible limitation of the study could be the on-line self-reported heights and weights. Nevertheless, according to the literature, there is a high correlation between self-reported and actual BMI in university students [55][56][57] and young adults with and without superior education [58-60].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents with high scores on depressive symptoms are 1.16 times more likely to develop DEB [ 16 ]. Among university students, DEB was associated with the presence of symptoms of depression [ 7 , 17 19 ] and anxiety [ 20 – 23 ]. Additionally, the interaction between anxiety and students’ place of residence explained the risk of bulimic behavior [ 24 ].…”
Section: Introductionmentioning
confidence: 99%